Historic overview of pandemic, COVID-19 and Nepal’s experience - Pathak, Krishna Prasad (KMC Research Journal, 2021)
Novel Corona Virus (COVID-19) is an infectious disease similar form of pneumonia/ SARSCoV-2- impacting globally. Purpose of this article is to review the published studies and gather of the current information aimed at COVID-19 situation of Nepal. We summarized the published papers from the web pages, Journals, Google search engine. We focused eight steps to prepare this article (Conceptualization of the research question, literature search, title/abstract and full text screening, data extraction, risk of bias assessment, evidence synthesis, dissemination, updatefollowing the model of Tricco et al., (2020) conducting rapid reviews. It is declared as a public health emergency. However, why COVID-19 did not catastrophically hit Nepal rather than USA, Brazil, India, Europe and North America, is unknown. The pandemic of COVID-19 is still increasing and has created panic along with its different waves. But, as the numbers of cases are increasing rapidly governments are struggling to increase health care facilities and health care workers. There are lots of hypotheses about an end of covid but no clear answer has come yet. Thus, a lot of scientific studies is required to find the truth. Nepalese health services are needed to strengthen than today and follow lockdown, isolation, social distance and an advance screening test kit around the country. Further we need to adapt digitalization of health care system to prevent contamination.